The status of water at the origin of conceptual and theoretical conflicts - YAMMAD , YOUSRA; BADDIH , Hindou (Revue du contrôle, de la comptabilité et de l’audit, 2024)
With the multiplication of ecological crises that have wreaked havoc throughout history, it was imperative to reconcile the model of economic development based on infinite growth with respect for ecological concerns, admitting that we live in a world with finite resources.; we are talking here about sustainable development that integrates the environmental dimension within the process of socio-economic development. Many authors have paid particular attention towards this coveted resource admitting that it commands the development of human societies, however, a crucial uprising seems to preoccupy all confused collars during international conferences. Indeed, it is necessary to clarify the nature of this resource which creates theoretical equivocations because of the confusion that it poses as for its status. The present paper aims at a better understanding of the status of water based on the literature review, in this sense, we will present crossed glances, by confronting some theorie